The Geometry of Mineralisation and Exploration Models for the Blackwater Mine in the Reefton Goldfield (The Australasian Institute of Mining and Metallurgy, 2000)
At Waiuta near Reefton there is a remarkable vein of quartz <1 m thick which, apart from small offsets on late-stage faults, is a sheet like body essentially continuous down-dip and along-strike for> 1 km. The vein strikes NNE and dips steeply west (032/78¦W). From 1906-1951 the Blackwater mine produced 740,404 ounces of gold from the vein, called the æBirthday ReefÆ, which was one third of the total production from Reefton Goldfield and the fourth largest gold mine in New Zealand. Within the mine the vein is disrupted into a series of northeast-plunging shoots by late-stage faults. Similar faults, but with larger displacements, were thought in the past to truncate the vein at the northern and southern ends of the mine. The implication of this fault dissection model is that offset remnants of the vein await discovery. This study investigated the geometry of the vein and its relationship to host-rock structures and late-stage faults. A new model considers folding and lithological variation in the host-rocks to be fundamental in controlling the scale and geometry of veining, but does not rule out the possibility of some late-stage fault dissection. The Birthday Reef truncates 200-400 m wavelength folds in Greenland Group host-rocks at c.10¦ angle, that results in variation in the structural properties of host-rocks along strike every ~1350-2500 m. The spacing of fold hinges in the wall-rock veins is equivalent to the strike length of historic mining, implying that the Birthday Reef is probably hosted in a single limb of a fold. Similar relationships between mineralisation and host-rock folds appear to be present elsewhere in the Reefton Goldfield (e.g. Capleston and Murray Creek group of mines). Exploration targets are located one fold wavelength (c.1350-2500 m) further along strike from the Blackwater mine and relatively barren rock is expected in between the mine and target areas. Refining the location of folds and different host rock lithologies, using geophysical data and quality geological mapping, is the key to reducing exploration risks and discovering further resources.